Superação da dormência de sementes de annona macroprophyllata e annona purpurea com o uso de reguladores vegetais - Ferreira, Gisela [UNESP]; De-La-Cruz-Chacón, Ivan; González-Esquinca, Alma Rosa (FapUNIFESP (SciELO), 2016)
Some Annonaceae seeds are known to exhibit dormancy mechanisms ranging from possible seed coat impermeability to physiological dormancy. Thus, the aim of this study was to evaluate the effects of gibberellin (GA) GA3 and GA4+7 + benzyladenine (GA4+7 + BA) application in seeds of Annona macroprophyllata Donn. Sm (papausa) and Annona purpurea Moc. & Sessé ex Dunal (chincuya). The experiment was performed by the application of GA3 and GA4+7 + BA on seeds in concentrations of 0, 200, 400, 500, 600, 800 and 1000 mg L-1. The regulators broke the dormancy of both species. However, application of the GA4+7 + BA mixture had more significant results, with greater increases in germination in A. macroprophyllata than in A. purpurea. Treatments that promoted the highest germinations were GA4+7 + BA at a concentration of 200 mg L-1 for A. macroprophyllata (77%) and 200 mg L-1 of GA4+7 + BA and 500 mg L-1 of GA3 for A. purpurea (30% and 29%, respectively). Rate index, mean time and frequency of germination were distinct for both species and both treatments. Although both GA3and GA4+7 + BA promote germination, the GA4+7 + BA mixture was more effective than GA3to overcoming seed dormancy of both species, A. purpurea has a harder dormancy than A. macroprophyllata.
Overcoming seed dormancy in annona macroprophyllata and annona purpurea using plant growth regulators
Keywords: Annona diversifolia; Annonaceae; GA3; GA4+7; Germination-Annonaceae; N-(phenylmethyl)-aminopurine